2015
DOI: 10.1111/gfs.12192
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the crude protein fractions of lucerne leaves and stems under different stand structures

Abstract: Protein degradability in forage legumes is of global importance because utilization efficiency of forage has economic and environmental consequences. However, there are no published studies on the effect of legume stand structure on differences in crude protein (CP) fractions. The main objective of the present research was therefore to investigate differences in CP fractions in leaves and stems of lucerne (Medicago sativa L.) during the growing season. Stand traits were measured over 2 years, and forage was sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 31 publications
10
20
0
Order By: Relevance
“…As expected, the DM, NDFom, ADFom and ADL of leaves and stems increased at the REP stage if compared with GW stage in agreement with the findings of Rebol e et al (2004) probably because the weather was warmer and drier as also observed by Molle et al (2003). On the other hand, CP, EE and WSC showed higher levels during GW if compared with REP stage partly in agreement with Hakl et al (2016) in their study on alfalfa chemical composition. Soluble protein (NPN + BSP) were higher (P < 0.05) in REP than in GW stage, also in agreement with Hakl et al (2016).…”
Section: Macro Compositionsupporting
confidence: 90%
See 2 more Smart Citations
“…As expected, the DM, NDFom, ADFom and ADL of leaves and stems increased at the REP stage if compared with GW stage in agreement with the findings of Rebol e et al (2004) probably because the weather was warmer and drier as also observed by Molle et al (2003). On the other hand, CP, EE and WSC showed higher levels during GW if compared with REP stage partly in agreement with Hakl et al (2016) in their study on alfalfa chemical composition. Soluble protein (NPN + BSP) were higher (P < 0.05) in REP than in GW stage, also in agreement with Hakl et al (2016).…”
Section: Macro Compositionsupporting
confidence: 90%
“…Soluble protein (NPN + BSP) were higher ( P < 0.05) in REP than in GW stage, also in agreement with Hakl et al . (). The magnitude of change in macro chemical composition was much higher for WSC in leaves whereas stems showed greater changes in DM, NDFom, ADFom, Ash and CP contents.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although differences in quality can be found between basal and apical portions of the stem throughout the growing season (Christian, Jones, & Freer, ), the quality of the stem as a whole organ is a matter of concern in the improvement of feeding value (Julier & Huyghe, ; Lenssen et al., ), given its large proportion by weight in lucerne hay. Recent research has also shown that leaves and stems differ in crude protein fractions, with stems showing higher concentrations of non‐protein and indigestible nitrogen, and lower content of true protein fraction than leaves (Hakl, Fuksa, Konečná, & Šantrůček, ). A specific selection for stem quality was supported by a recent genomewide association study, which suggested substantially different genetic control of forage quality traits in lucerne stems and leaves (Biazzi et al., unpublished data).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have determined the protein fractions of tropical grasses (Johnson, Reiling, Mislevy, & Hall, 2001), legumes (Kirchhof, Eisner, Gierus, & S€ udekum, 2010), grass-legume mixtures (Krawutschke et al, 2013), different varieties of legumes (Yu, Christensen, McKinnon, & Markert, 2003), botanical fractions of lucerne (Hakl, Fuksa, Kone cn a, & Santr u cek, 2016) and perennial ryegrass (Hoekstra, Struik, Lantinga, van Amburgh, & Schulte, 2008 Figure 1. The procedure for the biomass yield determination was previously described by Solati et al (2017).…”
Section: Introductionmentioning
confidence: 99%